Dose Optimization of Fluconazole After Initial Treatment Failure in Pulmonary Cryptococcosis in an Obese Patient with Type 2 Diabetes and Cirrhosis: A Case Report - Yang Y; Shang J; Xu S; Wang Z (Infection and Drug Resistance)
Yang Yang,1 Jin Shang,2 Shuyun Xu,2 Zhen Wang1 1Department of Pharmacy, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of ChinaCorrespondence: Zhen Wang, Email zhencp303@qq.comBackground: Pulmonary cryptococcosis is a fungal infection of the lungs, particularly challenging to treat in patients with multiple comorbidities such as obesity, type 2 diabetes, and cirrhosis. Fluconazole is a first-line medication for the treatment of pulmonary cryptococcosis, but currently there is a lack of clinical medication experience in obese patients with multiple comorbidities, especially in dose adjustment after treatment failure.Case Introduction: This case report describes the experience of fluconazole in the treatment of pulmonary cryptococcal infection in a 45-year-old Chinese male with obesity, type 2 diabetes, and cirrhosis. The patient had a history of antifungal therapy for two weeks before admission, but the cough and hemoptysis were not improved. The treatment failed. After admission, it was recommended to use a conventional dose of fluconazole as an antifungal regimen according to the guidelines. However, the treatment effect was still unsatisfactory, due to the patients’ cough, hemoptysis, and fever symptoms were not relieved. During this period, it was newly found that the patient had cirrhosis and type 2 diabetes and had not previously controlled blood glucose. Considering the above situation, combined with the pharmacokinetic characteristics of fluconazole and the patient’s weight reaching 113 kg, the team readjusted the fluconazole medication regimen, and ultimately, the pulmonary infection improved without significant adverse reactions.Results: We found that it was more suitable for patients with obesity to calculate the dose of fluconazole by the lean weight. By estimation, the patient was finally given a loading dose of 800 mg fluconazole, and his condition improved significantly. After two weeks of medication, it was adjusted to a maintenance dose of 600 mg until the pulmonary infection in the patient disappeared.Conclusion: This case suggests that fluconazole antifungal therapy for pulmonary cryptococcal infection should fully consider the risk of comorbidities in patients. If necessary, medication dosage can be adjusted according to weight, and it is recommended to use lean bodyweight for evaluation and optimization. In addition, close attention should be paid to liver and kidney function.Keywords: pulmonary cryptococcosis, fluconazole, antifungal therapy, dose optimization, obese, lean bodyweight